2020
DOI: 10.1007/s10549-020-05637-y
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for second breast cancer events in women with a personal history of breast cancer using breast MRI: a systematic review and meta-analysis

Abstract: Purpose-Women with personal history of breast cancer (PHBC) are currently recommended to receive annual mammography for surveillance of breast cancer recurrence or new primary. However, given issues in accuracy with mammography, there is a need for evolving evidencebased surveillance recommendations with supplemental imaging. In this systematic review, we compiled and compared existing studies that describe the test performance of surveillance breast MRI among women with PHBC. Methods-We searched PubMed and EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…A recent meta-analysis investigating the performance of breast MRI as a surveillance method for patients with a personal history of breast cancer concluded that the evidence is insufficient to recommend for or against the use of MRI in this setting. 35 That meta-analysis included mostly patients treated with BCS and analyzed the detection rates using the sum of ipsilateral and contralateral cancers, resulting in a higher pooled cancer detection rate compared with our results of 5.17 per 1000 examinations by using breast MRI.…”
Section: Discussionsupporting
confidence: 85%
“…A recent meta-analysis investigating the performance of breast MRI as a surveillance method for patients with a personal history of breast cancer concluded that the evidence is insufficient to recommend for or against the use of MRI in this setting. 35 That meta-analysis included mostly patients treated with BCS and analyzed the detection rates using the sum of ipsilateral and contralateral cancers, resulting in a higher pooled cancer detection rate compared with our results of 5.17 per 1000 examinations by using breast MRI.…”
Section: Discussionsupporting
confidence: 85%
“…Breast cancer generally has a favorable prognosis in developed countries, partly due to detection at early and asymptomatic stages, thanks to the establishment of screening practices and therapeutic advances [14,15]. Tools like the widely recognized Breast Cancer Risk Assessment Tool (BCRAT or Gail model) that were developed and adapted for the disparity in racial and ethnic groups in developed countries, in particular in the United States, have been proving to be challenging to adapt to developing countries [16,17], including Cameroon, where information about the epidemiology and diversity of dominant risk factors of breast cancer in female populations is often scarce [8,18].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of breast cancer in asymptomatic women through screening is aimed at detecting the disease when it is less invasive, reducing advanced stage-associated morbidity and its rate of mortality [14] [15]. Tools like the widely recognized Breast Cancer Risk Assessment Tool (BCRAT or Gail model) that were developed and adapted for the disparity in racial and ethnic groups in developed countries, in particular in the United States, has been proving challenging to adapt to developing countries [16] [17], including in Cameroon, where information about the epidemiology and diversity of dominant risk factors of breast cancer in female populations is often scarce [8] [18].…”
Section: Introductionmentioning
confidence: 99%